Density, group composition and encounter rates of humpback whales (Megaptera novaeangliae) in the eastern Comoros Archipelago (C2) - J. Ersts, Peter; Kiszka, Jeremy; Vély, Michel; Rosenbaum, Howard C. (J. Cetacean Res. Manage., 2020)
The Comoros Archipelago is an assemblage of oceanic islands, banks and offshore reef systems that longitudinally span the northern Mozambique Channel. The greater Comoros Archipelago has been designated by the IWC as Wintering sub-Region C2 for humpback whales and is currently considered data deficient. Since 1997, annual marine mammal surveys of varying length and objective have been carried out in the waters surrounding Mayotte, the eastern most island in the Comoros Archipelago. The humpback whales component of these surveys focused effort in and around the lagoon surrounding Mayotte. While it is expected that humpback whales can found throughout Comoros Archipelago it still remains unknown as to what degree humpback whales utilise specific banks and offshore reef systems within this area. Surveys conducted in 2002 and 2003 included passing mode and closing mode components intended to examine the density, group composition and encounter rates of humpback whales in an offshore reef complex and a bank adjacent to the lagoon surround Mayotte. The densities of humpback whales, out to one nautical mile from the surveyed transects, ranged from 0.027 to 0.618 whales/n.mile2 across three study sites. Females with calves were the most frequently encountered group type. Encounter rates ranged from 0.98 to 2.36 groups per hour of search effort. These results, while exploratory in nature, indicate that the eastern region of the Comoros may be an important area for humpback whales during the late austral winter months and that additional, more intensive systematic research is warranted.